Monitoring Processes for Training and Professional Activities Teaching Staff of Higher Educational Institutions - Begimkulov, Uzokboy; Shoymardonov, Tuymurod; Adashboev, Shavkiddin; Obidov, Azamat; Akilbaeva, Mukhtabar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper highlights the essence of monitoring as a basis of foreseeing the development of professional skills and processes of retraining and upgrading teachers’ professional skills. There are given types, objects, and methods of  the monitoring of teachers’ professional competence. There are described the possibilities of developed electronic monitoring system, as an innovative technology that enables to fulfill the descriptive, corrective and predictive functions of quality management in the system of upgrading teachers’ professional skills as well.